2015
DOI: 10.1016/j.neuron.2015.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Norepinephrine and Corticotropin-Releasing Hormone: Partners in the Neural Circuits that Underpin Stress and Anxiety

Abstract: Norepinephrine and corticotropin-releasing hormone (CRH) have long been implicated in the response to stress. In this issue of Neuron, McCall et al. (2015) show that CRH projections from the central amygdala drive tonic locus coeruleus activity that evokes acute anxiety responses and place aversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 16 publications
1
10
0
1
Order By: Relevance
“…Previous findings have suggested that IRES-mediated translation occurs in stressful conditions [28][29][30]. NE is the wellknown hormone responsible to this condition [64] and may increase the levels of hnRNP R; therefore, the novel role of hnRNP R on AANAT translation observed in our study suggests a possible regulation of circadian rhythms and melatonin synthesis during many dynamic physiological conditions. The novel fine-tuning roles of RNA-binding proteins including hnRNP R in AANAT and melatonin synthesis deserve further investigations.…”
Section: Discussionsupporting
confidence: 58%
“…Previous findings have suggested that IRES-mediated translation occurs in stressful conditions [28][29][30]. NE is the wellknown hormone responsible to this condition [64] and may increase the levels of hnRNP R; therefore, the novel role of hnRNP R on AANAT translation observed in our study suggests a possible regulation of circadian rhythms and melatonin synthesis during many dynamic physiological conditions. The novel fine-tuning roles of RNA-binding proteins including hnRNP R in AANAT and melatonin synthesis deserve further investigations.…”
Section: Discussionsupporting
confidence: 58%
“…In contrast to VLM CA neurons, which send heavy projections to the HPA axis and the sympathetic nervous system (Kvetnansky et al, 2009;Moore and Bloom, 1979;Rinaman, 2010), the LC sends intense projections to high cognitive centers such as the hippocampus and the cortex but sends few inputs to the PVN or the spinal cord (Moore and Bloom, 1979;Sawchenko and Swanson, 1982). Therefore, although the LC-CA system has been implicated in many stress-induced neuropsychiatric disorders such as anxiety, depression, and posttraumatic stress (McCall et al, 2015;Sara, 2009;Southwick et al, 1997;Sun et al, 2015), the role of the LC-CA system in controlling stress-induced hyperglycemia appears to be indirect or dispensable.…”
Section: Discussionmentioning
confidence: 99%
“…Among these hormones, CRF homolog DH-1 is suggested to be involved (Even et al, 2012). Two hormones in particular, octopamine and adipokinetic hormone (AKH) are believed to be stress hormones in insects, the former the equivalent of norepinephrine which is synthesized in the LC, a downstream target of CRF in mammals (Sun et al, 2015). LC activity is involved in generation of anxiogenic and aversive behaviours, innervating a wide range of centers implicated in these behavioural responses to stress (Sun et al, 2015).…”
Section: Rhopr-crf/dh and Reproductionmentioning
confidence: 99%